IMPLEMENTASI PROGRAM EKSTRAKURIKULER “BINA IMAN” DALAM PRESPEKTIF TOLERANSI SISWA MUSLIM DAN KATOLIK DI SMAS KATOLIK YOS SUDARSO KEPANJEN - Anggi Erika Dewi; Dwi Fitri Wiyono; Bagus Cahyanto (VICRATINA, 2022)
This research is a qualitative research with the type of case study research with the place of research at Yos Sudarso Catholic High School Malang. Data was collected using the methods of observation, interviews, and documentation. Data analysis is done by summarizing important data and then drawing conclusions. The program model of the "Bina Iman" extracurricular program at Yos Sudarso Kepanjen Catholic High School, namely the religious extracurricular model suggests that the "Bina Iman" extracurricular program model is a religious extracurricular model which in its implementation usually uses a lecture learning model, then training and practice as a complement and reinforce learning that has been taught. The process of implementing the "Bina Iman" extracurricular program at Yos Sudarso Catholic High School is by means of the steps taken by the teacher or coach of Yos Sudarso Kepanjen Catholic High School in the preparation of the lecture method including formulating specific instructional objectives, compiling lecture materials and then using the prepared material, in delivering lecture materials in class and using the media. In addition to explaining, the teacher or coach also gives tasks in this case as training related to lecture material, holding an assessment plan, usually practice and evaluation with the aim of knowing whether the goals that have been formulated can be achieved optimally.